THE WAYS TO ESTABLISH THE PERSONALITY ORIENTED PARADIGM IN THE UKRAINIAN SCHOOL EDUCATION (PSYCHO-PEDAGOGICAL ASPECT) - Dichek, Natalia (The Modern Higher Education Review, 2017)
In the context of representing the ideas of individualization of school education developed in Ukraine in the last third of the XX century and their implementation in the educational process, the poorly studied issue, namely, the Ukrainian psychologists’ contribution to the research of the ways and the means of teaching individualization that was conducted in the late 1980s – the first half of the 1990s was covered. The major areas of research in educational psychology, personality psychology that dealt with deepening learning individualization, that is, developing a system of differentiation of primary and secondary schools, the implementation of the applied psychology achievements, in particularly, the organization of psychological services in the school system, the study of the pupils’ creative potential, discovering and development of their talent as well as creative thinking were outlined. The analysis of the psychological and educational outcomes of the Ukrainian scholars proved the focus of the research on humanization of the educational process, the ways to ensure meeting the pupils’ individualized needs in the learning process that corresponded to the establishment of a personality oriented paradigm in the Ukrainian education.